The influence of organizational factors on construction risk among Malaysian construction industries - Adeleke, A. Q.; Sorooshian, Shahryar; Yao, Liu; Nawanir, Gusman; Azi Izwani, Nor Hamzah (UMP, 2019)
Extensive numbers of empirical studies have proven that certain organizational factors do influence construction risk management. In line with the recent substantial attention on risk management in Malaysia, and the demand for Malaysian construction industries to implement risk management in order to confront the challenges they are facing, studies on risk management in Malaysia construction industries are few. The objectives of this study are to assess the extent of construction risk management among construction industries operating in Kuantan Malaysia, and to examine the organizational internal factors influencing their risk management, moderated with organizational culture. A proportionate stratified random sampling was used to choose 107 construction industries acquired through construction industries development board Malaysia (CIDB). A total of 87 valid and completed questionnaires were returned, leading to 81 percent response rate. Descriptive statistics with 5-point Likert scale interpretation and PMBOK’s risk management category were used to attained the first objective this research. Extent of risk management among Malaysian construction industries was discovered to be at a high level. Following organisational control theory, this research also investigated the role of organizational culture on the relationship between organizational internal factors and construction risk management. Likewise, the moderating effects of organizational culture opined a positive relationship between organizational internal factors and construction risk management. Similarly, all the direct hypotheses relationship between organizational internal factors and construction risk management were supported. In summary, the findings in this research established that organizational culture can enhance risk management among construction industries operating in Malaysia. To augment risk management among construction industries, project managers should give considerable attention to the organizational internal factors discovered to be influencing their risk management.